2017
DOI: 10.3892/mmr.2017.7785
|View full text |Cite
|
Sign up to set email alerts
|

Adenoviral-bone morphogenetic protein-7 and/or doxazosin therapies promote the reversion of fibrosis/cirrhosis in a cirrhotic hamster model

Abstract: Liver fibrosis occurs in the presence of continuous insults, including toxic or biological agents. Novel treatments must focus on ceasing the progression of cellular damage, promoting the regeneration of the parenchyma and inhibition of the fibrotic process. The present study analyzed the effect of bone morphogenetic protein (BMP)-7 gene therapy with or without co-treatment with doxazosin in a model of liver cirrhosis in hamsters. The serum alanine aminotransferase, aspartate aminotransferase and albumin level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…The aim of this study was to enhance the understanding of the role of BMP6 in skin fibrosis using human and murine in vitro and in vivo model systems. Notably, previous studies of other BMP-subfamily members, especially BMP7, showed that their effects on fibrosis vary in a tissue-and cell-specific manner (Cervantes-Garcia et al, 2017;Higgins et al, 2017;Jin et al, 2018;Murray et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The aim of this study was to enhance the understanding of the role of BMP6 in skin fibrosis using human and murine in vitro and in vivo model systems. Notably, previous studies of other BMP-subfamily members, especially BMP7, showed that their effects on fibrosis vary in a tissue-and cell-specific manner (Cervantes-Garcia et al, 2017;Higgins et al, 2017;Jin et al, 2018;Murray et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The experiment began with two groups: (i) the intact (control) group (n=5) and (ii) the cirrhosis group (n=20). Cirrhosis was induced by the intraperitoneal administration of 50 mg/kg CCl4 in petrolatum, 2 times per week (n=20) for 20 weeks [17, 18]. Each animal was weighed once per week throughout the experiment.…”
Section: Methodsmentioning
confidence: 99%
“…The remaining 15 hamsters with cirrhosis were divided into three groups (n=5 each) with the following 4-week treatments: (1) carvedilol (1.2 mg/Kg/day, (2) doxazosin (1 mg/Kg/day, and (3) placebo (control of endogenous reversal) (Figure 1); the last one is important to check the activity of the adrenoblockers on hepatic cirrhosis and not only the efficiency of the animal model to reverse the damage on its own. The doses and frequency of administration were based on previous studies [17, 18]. Subsequently, the hamsters were sacrificed and the liver samples were fixed in neutral formalin at 4% for histological examination.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Carvedilol, a nonselective β -AR, and doxazosin, an α 1-AR blocker (antihypertensive drugs), show antifibrotic effects in in vivo studies [15, 16]. Likewise, it was reported that carvedilol increases risks for hepatorenal syndrome and acute kidney injury, reducing transplant-free survival in cirrhotic patients with spontaneous bacterial peritonitis [17], whereas doxazosin shows hepatotoxic effects in the cirrhotic livers of experimental animals [18, 19].…”
Section: Introductionmentioning
confidence: 99%